Disease-proof : the remarkable truth about what makes us well - Katz, David L., 1963- (Hudson Street Press, 2013)
In Disease-Proof, disease prevention expert Dr. David Katz reveals that we can slash our risk of every major chronic disease--heart disease, cancer, stroke, diabetes, dementia, and obesity--by 80 percent or more. But to get there, we need specific skills. This book arms us with what Dr. Katz calls skillpower: a user-friendly set of tools that will help us put this knowledge into action. Drawing upon the latest scientific evidence and decades of clinical experience, Dr. Katz shows us how to make lasting changes, from smart food swaps to figuring out what kind of exercise is right for us (and that will actually be enjoyable) to identifying and overcoming our particular health challenges.--From publisher description.